PENINGKATKAN HASIL BELAJAR PKN MATERI KEBEBASAN BERORGANISASI MELALUI MODEL PEMBELAJARAN PENEMUAN (DISCOVERY) (JS (JURNAL SEKOLAH), 2019)
Abstract: Learning Pkn Material Freedom of Organization Through the Learning Learning Model (Discovery). This research was conducted on grade V.C students of SD Negeri 2 Palembang in the 2016/2017 Academic Year with the aim of improving the learning outcomes of the freedom of organizing citizenship education (PKn) through the discovery learning method. The research subjects were students of Class V.C 2016/2017 Academic Year with a total of 29 students. From the results of the learning activities that have been carried out for two cycles, and based on all the discussions and analyzes that have been done, it can be concluded that learning by discovery has a positive impact in improving the learning outcomes of Civics students in SD Negeri 2 Palembang, which is marked by an increase in students' learning completeness in each cycle, namely pre cycle of 51.72%, cycle I (72.41%) and cycle II (86.21%).Keywords: Learning Outcomes, Civics, Discovery Model.Abstrak: Belajar Pkn Materi Kebebasan Berorganisasi Melalui Model Pembelajaran Penemuan (Discovery). Penelitian ini dilakukan terhadap siswa kelas V.C SD Negeri 2 Palembang Tahun Pelajaran 2016/2017 dengan tujuan untuk meningkatkan hasil belajar materi kebebasan berorganisasi pendidikan kewarganegaraan (PKn) melalui metode discovery learning. Subjek penelitian adalah siswa-siswa kelas V.C Tahun Pelajaran 2016/2017 dengan jumlah siswa 29 orang. Dari hasil kegiatan pembelajaran yang telah dilakukan selama dua siklus, dan berdasarkan seluruh pembahasan serta analisis yang telah dilakukan dapat disimpulkan pembelajaran dengan penemuan (discovery) memiliki dampak positif dalam meningkatkan hasil belajar PKn siswa SD Negeri 2 Palembang yang ditandai dengan peningkatan ketuntasan belajar siswa dalam setiap siklus, yaitu pra siklus sebesar 51,72%, siklus I (72,41%) dan siklus II (86,21%).Kata Kunci: Hasil Belajar,PKn, Model Discovery.